The physiological benefits of sitting less and moving more: Opportunities for future research - Hwang, Chueh-Lung; Chen, Szu-Hua; Chou, Chih-Hsuan; Grigoriadis, Georgios; Liao, Tzu-Chieh; Fancher, Ibra S.; Arena, Ross; Phillips, Shane A. (Progress in cardiovascular diseases, 2022)
Sedentary behavior (SB) and physical activity (PA) are important risk factors of cardiovascular disease morbidity and mortality. In addition to increasing the amount of moderate-to-vigorous PA (MVPA), the current PA guidelines recommend that adults should reduce SB, or any waking activity performed while sitting, reclining, or lying, with low energy expenditure. While mounting evidence has emphasized the benefits of increasing MVPA, little has focused on the effect of SB on health. Therefore, this review discusses the pathophysiological effects of SB and the potential physiological benefits of reducing/breaking up SB at the levels below the current guidelines for PA. Such knowledge is important, given that the majority of the United States population performs insufficient or no MVPA and is at high risk of being negatively impacted by SB. Interventions targeting sedentary time, such as breaking up SB by standing and moving, may be safe, feasible, and applicable to execute daily for a wide range of the population. This review also discusses the importance of monitoring SB in the era of the coronavirus disease 2019 (COVID-19) pandemic and the clinical implications of sitting less and moving more.